Highly Dispersed WOx/SiO2 Catalysts Derived from W-TRIS Complex for Efficient Biobutadiene Production from Acetylene-Ethylene Cross-Metathesis - Pratya Promchana; Kittisak Choojun; Kanokwan Wengwirat; Wanwisa Limphirat; Tawan Sooknoi (Industrial & Engineering Chemistry Research, 2025)
Renewable 1,3-butadiene was selectively produced via acetylene-ethylene cross-metathesis over highly dispersed WOx/SiO2 catalysts prepared by a simple impregnation method using the molecular precursor (NH4)2[W2O6(TRIS)2] (W-TRIS). Compared to catalysts derived from ammonium metatungstate (AMT), the TRIS-derived catalysts exhibited superior WOx dispersion and catalytic activity, attributed to stronger W–O–Si interactions as evidenced by XRD, DRUV–vis, Raman spectroscopy, and W L3-edge XANES/EXAFS. Systematic variation of WO3 loading revealed that 5 wt % WOx/SiO2-TRIS offered the optimal balance of activity and selectivity, achieving 60% acetylene conversion, ∼74% selectivity to 1,3-butadiene, and a turnover frequency (TOF) of 23 h–1. Contact time analysis confirmed that 1,3-butadiene was the primary product, while minor byproducts such as cyclohexene and benzene originated from Diels–Alder cycloaddition followed by dehydrogenation. Reaction temperature screening identified 450 °C as the optimal operating condition; higher temperatures led to increased side reactions. Importantly, long-term testing over 100 h under continuous-flow conditions demonstrated high stability with sustained selectivity and negligible coke formation. These findings underscore the practical advantages of the W-TRIS molecular precursor strategy in designing durable WOx/SiO2 catalysts for efficient and sustainable C4 chemical production from bioethylene.
Keywords: Synthetic Organic Chemistry Methods; Catalysis for Biomass Conversion; Catalysis and Hydrodesulfurization Studies